EXCLUSION OF A LARGE RUPTURED SUPERFICIAL FEMORAL ARTERY ANEURYSM WITH TWO ENDOPROTHESIS OUTSIDE THE “INSTRUCTIONS FOR USE” - Correia, Mafalda (2020)
Introduction: We present the case of a superficial femoral artery ruptured aneurysm treated with an endoprothesis outside the “Instructions for Use”. Case report: 83 years old patient with sequential rupture of both superficial femoral arteries aneurysms. In the right limb the patient was submitted to conventional bypass surgery that resulted in an extended recovery period. An endovascular approach was the choice to treat the left ruptured superficial femoral artery aneurysm. The patient was submitted to aneurysm exclusion with two Endurant™II Medtronic® endoprothesis. At two-year follow-up the patient is asymptomatic and the aneurysm remains excluded with no endoleaks. Conclusions: Despite outside “Instructions for Use”, the use of an endoprothesis to treat SFA ruptured aneurysm presented as limb salvage procedure with excellent technical success and medium-term results.